Design and simulation of RF-CMOS spiral inductors for ISM band RFID reader circuits - Uddin, Md. Jasim; Nordin, Anis Nurashikin; Ibrahimy, Muhammad Ibn; Reaz, Mamun Ibn; Zulkifli, Tun Zainal Azni; Hasan, Muhammad Asfarul (2009)
The recent popularity of RFID tags has generated research for accompanying miniature, low-power reader circuits. This work illustrates the design of RF complementary metal- oxide-semiconductor (CMOS) process compatible spiral inductors. Several simulators such as AWR Microwave Officereg, SONNETreg, and finite element program CST were used to provide its S21 and S31 transmission characteristics, approximate and finalized design layout values respectively. This design utilized Silterra 0.18 mum RF-CMOS technology process parameters. Simulation results indicate that inductors core diameters must be adequately large (more than 100 mum) to ensure high quality factor characteristics and its conductor spacing should be minimal to obtain larger per unit area inductive value. The proposed design methodology optimizes the conductor width of inductors to allow alignment of the peak quality factor with the circuit's operating frequency, thereby enhancing the input/output matching characteristics and S-parameter extraction in the GHz region.